Use of 3D Printing in Complex Spinal Surgery: Historical Perspectives, Current Usage, and Future Directions. Issue 3 (September 2016) - Grant, Caroline A.; Izatt, Maree T.; Labrom, Robert D.; Askin, Geoffrey N.; Glatt, Vaida
Abstract : Three-dimensional (3D) printing has been used in complex spinal surgical planning since the 1990s and is now increasingly utilized to produce surgical guides, templates, and more recently customized implants. Surgeons report beneficial impacts using 3D-printed biomodels as a preoperative planning aid as it generally provides for a better representation of the patient's anatomy than on-screen viewing of computed tomography or magnetic resonance imaging. Furthermore, it has proven to be very beneficial in surgical training, and in explaining complex deformity and surgical plans to patients/parents. This paper reviews the historical perspective, current use, and future directions in using 3D printing in complex spinal surgery cases. This review reflects the authors' opinion of where the field is moving in light of the current literature. Despite the reported benefits of 3D printing for surgical planning in the recent years, it remains a highly niche market. This review raises the question as to why the use of this technology has not progressed more rapidly despite the reported advantages—decreased operating time, decreased radiation exposure to patients intraoperatively, improved overall surgical outcomes, preoperative implant selection, as well as being an excellent communication aid for all medical and surgical team members. Increasingly, the greatest benefits of 3D-printing technology in spinal surgery are custom designed drill guides, templates for pedicle screw placement, and customized patient-specific implants. With applications such as these, 3D-printing technology could potentially revolutionize health care in the near future.